Navigating Human Resource Challenges in Madrasah: Implications for Islamic Education Policy Implementation - Mawardi; Candra; Kumaidi (Journal of Educational Management Research, 2023)
This study aims to analyze managerial problems and structural barriers in the management of human resources (HR) in madrasas and their implications for the implementation of the latest Islamic Education policy. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews with madrasah principals, vice principals, and teachers, observations of managerial practices and learning, and documentation studies related to HR management. Data analysis was carried out through the stages of data condensation, data presentation, and continuous verification of findings. The results show that HR management in madrasas is still dominated by an administrative and reactive orientation, exacerbated by a rigid bureaucratic structure and limited access to professional development. This condition results in a mismatch between the competencies of educators and Islamic Education policy standards and impacts the implementation of policies that are not uniform across learning levels. The implications of this study emphasize the importance of strengthening competency-based HR management, structural flexibility, and continuous professional development programs to improve the effectiveness of Islamic Education policies in madrasas.